Speech Prosody 2016 2016
DOI: 10.21437/speechprosody.2016-82
|View full text |Cite
|
Sign up to set email alerts
|

In search of the role's footprints in client-therapist dialogues

Abstract: The goal of this research is to identify speaker's role via machine learning of broad acoustic parameters, in order to understand how an occupation, or a role, affects voice characteristics. The examined corpus consists of recordings taken under the same psychological paradigm (Process Work). Four interns were involved in four genuine client-therapist treatment sessions, where each individual had to train her therapeutic skills on her colleague that, in her turn, participated as a client. This uniform setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Moreover, the comparison of the three sessions to session BM demonstrates that the role of the speaker does not necessarily entail the participation level, and therefore power relations cannot directly be derived from these durational parameters. In Lerner, Silber-Varod, Batista, and Moniz (2016), we examined the same sessions in a more complex way, using computational learning methods on acoustic parameters. We found that at the beginning of each session there were more differences in the acoustic variables between the two speakers than there were in the middle of the session while the least differences were found at the final part of the session.…”
Section: Analysis By Visualization: Conversation Infographicsmentioning
confidence: 99%
“…Moreover, the comparison of the three sessions to session BM demonstrates that the role of the speaker does not necessarily entail the participation level, and therefore power relations cannot directly be derived from these durational parameters. In Lerner, Silber-Varod, Batista, and Moniz (2016), we examined the same sessions in a more complex way, using computational learning methods on acoustic parameters. We found that at the beginning of each session there were more differences in the acoustic variables between the two speakers than there were in the middle of the session while the least differences were found at the final part of the session.…”
Section: Analysis By Visualization: Conversation Infographicsmentioning
confidence: 99%